Persiapan Dan Perencanaan Pembangunan Jaringan Intranet Di Gardu Induk Aset PT PLN (Persero) Unit Pelaksana Transmisi Banjarbaru - Nabila, Alifah (Journal Information Technology Trends (JITRENDS), 2024)
Intranet is a network technology that applies the concept of a local network (LAN) by adopting internet technology. Because it applies the LAN concept, the Intranet network only applies to a fairly small scope. In this study, researchers used the PPDIOO method in practice. This research aims to optimize data management and confidentiality at twenty-six asset substations belonging to PT PLN (Persero) Unit Pelaksana Transmisi Banjarbaru with plans to build an intranet network at each substation. With this intranet network, PT PLN (Persero) Unit Pelaksana Transmisi Banjarbaru finds it easier to manage communications and maintain data confidentiality because it can only be accessed by employees or workers connected to the local network